Localized drag modification in a laminar boundary layer subject to free-stream travelling waves via critical and Stokes layer interactions. (25th April 2022) - Agarwal, T.; Cukurel, B.; Jacobi, I.
Abstract: Abstract : Perturbation of the laminar boundary layer by free-stream travelling waves was shown to produce highly-localized skin friction modification via steady streaming. The forced boundary layer flow was calculated numerically and studied as a function of the phase speed, frequency and amplitude of the perturbations. Upstream-travelling waves always produced negative streaming, whereas downstream-travelling waves produced positive or negative streaming that varied with forcing strength and streamwise location. The sign of the resultant streaming was explained in terms of the inclination of the induced velocity modes, which evolved spatially in response to the streamwise variation and overlap of the Stokes and critical layers.